Functional Nanocarbon Hybrids for Optoelectronic Applications - Debes, Paul Peter; Justus Liebig University Giessen (My University, 2025)
Carbon dots (CDs) are carbon nanomaterials with remarkable photoluminescence, tunable surface chemistry, and high biocompatibility, making them attractive for applications in catalysis, sensing, and biomedicine. This work presents a comprehensive investigation of the synthesis, surface functionalization, characterization, and application of CDs, with a particular focus on carbon nanodots (CNDs). The broad objective was to understand how precise surface modifications and advanced analytical techniques could reveal structure-property relationships and unlock application potentials. CNDs were synthesized using bottom-up methods that allow precise control over particle morphology and surface functionalities. A major focus was the quantification of surface functional groups for covalent modification strategies. In Publication 1, the question of whether the total amount of primary amines on the surface correlates with the efficiency of amide coupling reactions was addressed. Using a combination of the Kaiser test and quantitative 19F-NMR spectroscopy, it was found that coupling efficiency does not scale directly with the apparent amine content. Instead, steric accessibility and reactivity were identified as critical factors governing surface functionalization. These findings provide a basis for the rational selection of linkers and optimization of reaction conditions in covalent surface chemistry. Publication 2 focused on whether covalent attachment of organic dyes to CNDs could improve their stability and integration into photocatalytic systems. The study demonstrated that covalent dye-CND hybrids, when integrated into TiO2-based hybrid photocatalysts, exhibited reduced dye leaching and consumption, thus advancing the development of more sustainable and long-lasting photocatalytic systems. In Publication 3, the focus was on how the photophysical behavior of CND-azobenzene hybrids can be modulated by structural design, including a spacer and connectivity. It was shown that the molecular spacer significantly influences the electronic coupling and fluorescence quenching behavior and enables reversible photoisomerization. These results underline the potential of these hybrid materials for light-controlled applications such as optostimulation and targeted biotechnological processes. The results highlight the importance of surface engineering in tailoring CNDs-hybrids. Combining surface analysis, targeted covalent modification, and application-driven hybrid design provides the foundation for solving challenges in photocatalysis, bioimaging, and stimuli-responsive nanotechnology.
Funktionale Nanokohlenstoff-Hybride für optoelektronische Anwendungen
Keywords: Carbon Nanodots; Amide Coupling; Photocatalysis; Bio-applications; Nanocarbon Hybrids; ddc:540; ddc:500